PENGARUH NILAI TUKAR RUPIAH, HARGA KOMODITAS EMAS DAN MINYAK BUMI TERHADAP RETURN SAHAM PT ANEKA TAMBANG Tbk - , Darius Darmawan Kuntara, Drs. Anis Baridwan, MBA ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Investment is a rational course of action. It implies that investors - individually or through companies - in determining and establishing good investment in one or several companies need to consider micro economic factors (internal factors) and macro economic factors (external factors). One of the micro economic factors that should be taken into consideration is financial statement . On the other hand, the macro economic factors (external factors) are inflation rate, interest rate, currency rate, GDP deflator, and comodity cost. Some assumptation from a security analyst has provided the inspiration for this writing. It said that rise in gold value will increase the share profit of Aneka Tambang company (Antam). Then, the effects of inflation rate, interest rate, currency rate, GDP deflator, and comodity cost on the share profit of Antam will be investigated, analysed, and evaluated. The data sample used in this study is secondary data. Research model used in this study is time series weekly model. This study had been conducted from17 July 2007 to 31 March 2010. This is a dependent variable - based study of the share profit of Antam and an independent variable - based study of the currency rate, gold and oil comodity cost. SPSS 17.00 was used to estimate the result of linear regresion model though test t. The significance has been identified from those variables. By using SPSS 17.00, the results found from the study is that the gold comodity cost movement did not effect significantly as well as did not move positively side by side with the share profit of Antam. However, the oil comodity cost movement and the share profit of Antam significantly did. Meanwhile, this was different from the currency rate movement. On the other hands, as what the experts say that the currency rate movement brings effect negaitively on the share profit of Antam but the currency rate movement and the share profit of Antam do not move in rows.